Measuring social desirability across language and sex: A comparison of Marlowe–Crowne Social Desirability Scale factor structures in English and Mandarin Chinese in Malaysia. Issue 2 (11th May 2016) - Kurz, A. Solomon; Drescher, Christopher F.; Chin, Eu Gene; Johnson, Laura R.
Abstract : Malaysia is a Southeast Asian country in which multiple languages are prominently spoken, including English and Mandarin Chinese. As psychological science continues to develop within Malaysia, there is a need for psychometrically sound instruments that measure psychological phenomena in multiple languages. For example, assessment tools for measuring social desirability could be a useful addition in psychological assessments and research studies in a Malaysian context. This study examined the psychometric performance of the English and Mandarin Chinese versions of the Marlowe–Crowne Social Desirability Scale when used in Malaysia. Two hundred and eighty‐three students (64% female; 83% Chinese, 9% Indian) from two college campuses completed the Marlowe–Crowne Social Desirability Scale in their language of choice (i.e., English or Mandarin Chinese). Proposed factor structures were compared with confirmatory factor analysis, and multiple indicators–multiple causes models were used to examine measurement invariance across language and sex. Factor analyses supported a two‐factor structure (i.e., Attribution and Denial) for the measure. Invariance tests revealed the scale was invariant by sex, indicating that social desirability can be interpreted similarly across sex. The scale was partially invariant by language version, with some non‐invariance observed within the Denial factor. Non‐invariance may be related to differences in the English and Mandarin Chinese languages, as well as cultural differences. Directions for further research include examining the measurement of social desirability in other contexts where both English and Mandarin Chinese are spoken (i.e., China) and further examining the causes of non‐invariance on specific items.